Real-life survey on severe asthma patients during COVID-19 lockdown in Italy. (3rd August 2021) - Caruso, Cristiano; Colantuono, Stefania; Urbani, Sara; Heffler, Enrico; Canonica, Giorgio Walter; Andriollo, Gloria; Di Michele, Loreta; Scarlata, Simone; Zennaro, Danila; Rigon, Amelia; Vadacca, Marta; Moroni, Rossana; et al.
ABSTRACT: Introduction : The SARS-CoV-2 pandemic has deeply revolutionized our lives and consequently the management of patients, specifically ones with severe asthma. Objective : A survey was conducted to evaluate the effects on adherence, exacerbations and quality of life in patients with severe asthma during the COVID-19 pandemic period. Methods : 100 severe asthma patients, who accepted to participate to the survey, were asked to respond to different questionnaires in order to assess asthma symptoms (Asthma Control Test – ACT, and Asthma Control Quality – ACQ) and rino-sinusal ones (Sino-nasal outcome test – SNOT-22). Results : 31 out of 100 patients reported worsening of respiratory symptoms requiring a step-up in therapy dosage or frequency during the observational period; however, exacerbation rate was very low. Only 17 (17%) of the 100 participants experienced a severe asthma exacerbation. Moreover, there was no confirmed diagnosis of COVID-19 in this population. Conclusion : Patients with severe asthma did not show higher rates of exacerbations during the pandemic outbreak as well as no increased risk of contracting COVID-19 infection or developing the disease. Self-administration of biological drugs could be useful to maintain high rates of adherence to therapy, and, at the same time, to decrease the risk of exacerbations or Intensive Care Unit (ICU) room access.